TYPES OF SYNTACTIC RELATIONS IN A SENTENCE (Modern education and development, 2024)
The various syntactic interactions that influence sentence form in natural languages are examined in this article. We want to shed light on how meaning is constructed within sentences by examining components and their relationships. We go over the importance of key syntactic relationships for understanding language processing, such as subject-verb, verb-object, and modifiers.